Implementasi Kebijakan Sekolah Dalam Perencanaan, Pelaksanaan, Dan Evaluasi Pembelajaran Anak Berkebutuhan Khusus Di SLB Pamardi Putra - Haifa ‘Inayatun ‘Azizah; Dinda Kardila; Farah Fadhilah Fatih; An-Nisa Apriani (CV. SINAR HOWUHOWU, 2025)
Special Needs Schools (SLB) play a strategic role in providing educational services for students with special needs who have diverse characteristics and needs. Learning in SLB remains based on national policies and curricula, but its implementation is adapted to the abilities, needs, and conditions of students. This article aims to describe school policies in planning and implementing learning in SLB, the role of the principal in supporting teacher performance, factors supporting the educational process, student characteristics, learning methods, evaluation systems, and the role of parents in supporting children's education. The research method used is descriptive qualitative with a field study approach through observation and interviews. The results of the study indicate that learning flexibility, collaboration between stakeholders, and the application of a humanistic approach are key factors in the successful implementation of education in SLB.